Strengthening Differentiate Learning Using Ethnomathematics in the Implementation of the Independent Curriculum - Ari Irawan; Chatarina Febriyanti; Akbar Muchbarak (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to strengthen teacher knowledge related to differentiation learning. The technology used in this activity results from research in the form of an ethnomathematics application that is used to facilitate teachers in conducting assessments of students to classify students according to learning styles and student characteristics. This community service method is carried out using 3 stages, namely preparation, implementation, and evaluation. The results of this community service activity are 1) the teacher understands techniques and strategies in classifying student characteristics, 2) the teacher is able to use information and communication technology-based learning tools using an android smart tree, 3) the teacher is able to create teaching modules by implementing good practices in differentiated learning.